(untitled) (Medico Legal Update, 2021)
The variation in the wool traits of Iraqi sheep is very large and is affected by non-genetic and genetic factors. The study was carried out in the fields of Al-Kafeel station in Karbala governorate on a sample consisting of 26 heads of local Arabian sheep to find out the relationship between wool production (raw wool weight, clean wool weight) and some of its physical traits (tuft length, fiber length, fiber diameter) with some Blood components (glucose, total protein, growth hormone, thyroxine hormone), as the results showed a positive significant regression of the raw and clean wool weight and the diameter of the fiber on the percentage of glucose in the blood and with a regression coefficient of 0.117, 0.023, and 0.224 respectively, while the two traits of the strand length and the length of the fiber did not record a significant regression on the level of glucose in the blood.